Pasteuria penetrans (Bacilli: Bacillales: Pasteuriaceae) - Ruhiyyih Dyrdahl-Young; Peter DiGennaro (EDIS)
Includes: Introduction - Distribution - Description - Life Cycle and Biology - Hosts - Economic Importance - Management - Selected References